Articular Surface Failure of a Hybrid Anatomic Glenoid Component: A Case Report. Issue 3 (July 2021) - Yoon, Joo Hee; Marigi, Erick M.; Crowe, Matthew M.; Ortiguera, Cedric J.; Schoch, Bradley S.
Abstract : Case: We present a case of a 71-year-old woman with history of left-sided shoulder arthritis who underwent standard total shoulder arthroplasty using a novel hybrid glenoid component. After 3 years, she sustained traumatic dissociation of the interface between the polyethylene face and central titanium post, a unique failure mechanism of the hybrid glenoid component. This was successfully corrected through conversation to reverse shoulder arthroplasty (RSA). Follow-up after 2 years demonstrated marked improvement in pain and function. Conclusion: Hybrid glenoid components present a unique failure mechanism as compared to traditional glenoid loosening and can be effectively corrected with RSA.